Can action research strengthen district health management and improve health workforce performance? A research protocol - Mshelia, C.; Huss, R.; Mirzoev, T.; Elsey, H.; Baine, S.O.; Aikins, M.; Kamuzora, P.; Bosch-Capblanch, X.; Raven, J.; Wyss, K.; Green, A.; Martineau, T. (BMJ Open, 2013)
Introduction: The single biggest barrier for countries in sub-Saharan Africa (SSA) to scale up the necessary health services for addressing the three health-related Millennium Development Goals and achieving Universal Health Coverage is the lack of an adequate and well-performing health workforce. This deficit needs to be addressed both by training more new health personnel and by improving the performance of the existing and future health workforce. However, efforts have mostly been focused on training new staff and less on improving the performance of the existing health workforce. The purpose of this paper is to disseminate the protocol for the PERFORM project and reflect on the key challenges encountered during the development of this methodology and how they are being overcome. Methods: The overall aim of the PERFORM project is to identify ways of strengthening district management in order to address health workforce inadequacies by improving health workforce performance in SSA. The study will take place in three districts each in Ghana, Tanzania and Uganda using an action research approach. With the support of the country research teams, the district health management teams (DHMTs) will lead on planning, implementation, observation, reflection and redefinition of the activities in the study. Taking into account the national and local human resource (HR) and health systems (HS) policies and practices already in place, 'bundles' of HR/HS strategies that are feasible within the context and affordable within the districts' budget will be developed by the DHMTs to strengthen priority areas of health workforce performance. A comparative analysis of the findings from the three districts in each country will add new knowledge on the effects of these HR/HS bundles on DHMT management and workforce performance and the impact of an action research approach on improving the effectiveness of the DHMTs in implementing these interventions. Discussion: Different challenges were faced during the development of the methodology. These include the changing context in the study districts, competing with other projects and duties for the time of district managers, complexity of the study design, maintaining the anonymity and confidentiality of study participants as well as how to record the processes during the study. We also discuss how these challenges are being addressed. The dissemination of this research protocol is intended to generate interest in the PERFORM project and also stimulate discussion on the use of action research in complex studies such as this on strengthening district health management to improve health workforce performance.
Keywords: health management; health workforce performance; sub-Saharan Africa (SSA)